Instituições de segurança pública e práticas psicológicas : a segurança emocional dos agentes de segurança - Lira, Wellington Martins de (2011)
The crisis in public security in Brazil looks directs calls to the security forces. Experts say the isolation and failure of those who are not ready for democracy and the demands of the contemporary world. The public security officers, paradoxically, often have provoked violence, rather than fight it, and elite groups that come starring unwholesome actions. A former member of the Military Police of Pernambuco, and starting with a motivation incarnated in the body itself, as it suffered the pain inflicted on the skin to the public security officers, both by nature and by function of institutional dynamics, the author proposed to launch a fresh perspective on the topic, seeking a joint institution of a triangulation between public safety, psychological practice and the term that we coined as "emotional safety". Experience as an agent of public safety, coupled with the psychological training and studies and research developed by several authors contributed to the understanding of the field to be investigated and, therefore, conducted interviews with twelve semidirected professional psychologists and twelve public security officers of Pernambuco State, all in the Metropolitan Region of Recife. Through a comprehensive approach and analysis of the explicit content in thematic areas and units of meaning, the narratives of respondents provided an understanding that, despite efforts by professional psychologists and the perceived need by the public security agents, the action clinical psychology is still minimum in relation to need, as claimed by both segments. The lack of an adequate perception of the institution of public security on the importance of the psychological dimension has contributed to the suffering of security officers and psychologists, and interfered in the results of their practices. The stakes are high and overcoming it certainly will contribute significantly to public safety and civic life called pact, adopted by the Government of Pernambuco. We hope the results of this research contribute to the formation of a critical and reflective action of professional psychologists in the public security institutions, improving the quality of services aimed at society, by contributing to the actors and managers that segment